Respons Imunoglobulin-G dan Imunoglobulin-M Mencit yang Diberi Ekstrak Methanol Alga Biru Hijau dan Diinfeksi Dengan Takizoit - Simanjuntak, Sorta Basar Ida; Moeljopawiro, Sukarti; Artama, Wayan Tunas; Wahyuono, Subagus (Jurnal Veteriner, 2012)
Toxoplasmosis is an infectious disease caused by Toxoplasma gondii. This disease could severelyaffect humans and animals. Up to now there has been no simple treatment to fight toxoplasmosis. Aprospective alternative treatment to overcome this problem is by increasing immunity of the body using animmunostimulant such as Spirulina platensis. The aims of this research were to observe the potency of S.platensis as an immunostimulant and to find the most potential fraction of S. Platensis that can increasethe responses of IgG and IgM antibodies againts toxoplasma. The responses of these antibodies weremeasured using ELISA method. The isolation of compounds from S. platensis using Preparative ThinLayer Chromatography (PTLC) found three fractions which were a top fraction (I), a middle fraction (II),and a lower fraction (III). Forty-eight mice used in this research were divided into four different groupswith 12 mice in each group and treated differently. The top, middle, and lower fractions of S. platensis wereadministered orally to three groups of mice respectively at dose of 3mg/ml for each mouse while the micein the fourth group were kept as untreated controls. The treatment was conducted for 14 days consecutivelyand on the next day, all mice, including the controls, were challenged with tachizoit. The effect of S.platensisfractions on the responses of IgG and IgM antibodies were then measured at various time intervals, i.e. day0 (before infection) and day 1, 2, and 3 after infection. The results showed that IgG response increased inthe day 0 (2.504 OD) and the day 3 after infection (2.608 OD) while IgM response increased in day 1 afterinfection (2.898 OD). In conclusion, S. platensis was an immunostimulant and the middle fraction (II) of S.Platensis was the most potential fraction to increase immunity againts toxoplasma .
Keywords: immunity, immunostimulant, Spirulina platensis, tachizoit, toxoplasmosis